Reformulating Indonesian Bankruptcy Law: Substantive Justice and Good Faith - Sisca Utami Damajanti (jfpublisher, 2026)
Indonesian bankruptcy law, governed by Law Number 37 of 2004, was designed to balance creditor rights with debtor rehabilitation while ensuring orderly insolvency resolution. However, two decades of implementation reveal systemic dysfunction whereby formalistic judicial interpretation has transformed the law into an instrument of strategic litigation rather than equitable dispute resolution. This normative legal research employs statutory, conceptual, case study, and comparative approaches to deconstruct the prevailing application and propose comprehensive reformulation. The study identifies pervasive judicial formalism as the fundamental pathology, wherein courts mechanically apply technical default criteria without substantive inquiry into genuine insolvency or business viability. This enables widespread abuse through strategic bankruptcy filings by competitors and creditors pursuing collateral objectives, resulting in premature liquidation of viable enterprises and substantial economic waste. The research establishes that effective reform requires anchoring the system in two interdependent principles: substantive justice, mandating holistic assessment of debtor financial condition and restructuring prospects beyond procedural compliance, and good faith, functioning as rigorous procedural gatekeeper to filter abusive petitions. Implementation necessitates legislative amendments refining insolvency definitions, explicitly requiring good faith examination, and strengthening rehabilitation mechanisms. Judicial capacity enhancement through specialized training in financial analysis and institutional innovations including dedicated insolvency divisions prove essential. This reformulation framework transforms Indonesian bankruptcy law from strategic weapon into credible instrument serving economic efficiency, commercial justice, and constitutional values, thereby supporting Indonesia's developmental trajectory and investment climate enhancement.